(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
The article consists of theories about the practice of technologies that ensure personality development in the preschool education system at the world level, provide necessary knowledge to preschool children in accordance with their age, develop their cognitive process, rhetorical abilities. is being implemented.